How Islamic Education Synergizes with Semi-Military Education in Compulsory Boarding Programs: Evaluative Studies in Compulsory Boarding Programs in Vocational High Schools - Dinarti Srie Handayani; Sahraini Sahraini; Sukirman Sukirman (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research evaluates the effectiveness of the boarding and semi-military compulsory education program at SMK Negeri 3 Palopo in forming discipline and responsibility and increasing student achievement within the framework of Islamic educational values. Using a descriptive qualitative research approach, data collection was carried out through observation, in-depth interviews, and documentation studies involving teachers, staff, and students. The findings show that the program effectively increases students' discipline and motivation in learning and integrates Islamic values such as togetherness, honesty and social responsibility into students' lives. Although this research highlights the positive impact of these programs, it also suggests the need to improve supporting facilities such as libraries and laboratories and communication between schools and parents to support the effectiveness of the programs further. This research implies that deeper integration of Islamic values, coupled with improved infrastructure and increased parental support, can optimize boarding and semi-military education programs, cultivating graduates who are academically successful, of noble character and responsible, in line with the goals of Islamic education holistic. The study involved 25 participants, including teachers, staff, and students, providing a comprehensive picture of the program's impact.